2019
DOI: 10.1055/s-0039-1692687
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Recurrence Rate of Trigeminal Neuralgia after MVD and the Related Factors

Abstract: The aim of this article is to investigate the related factors affecting the recurrence of microvascular decompression (MVD) after trigeminal neuralgia. We selected 400 cases of patients who met the diagnostic criteria of primary trigeminal neuralgia. The recurrence rate of patients and their statistical data related factors such as age, gender, disease duration, pain branches, vascular compression, patients, and complications (urban and rural), were collected. Of the 400 cases, 36 had recurrence after 2 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The recurrence rate of thermoablation is 15% after 1 year of thermoablation, while MVD shows 8.4% after 2 years of surgery [16,17].…”
Section: Discussionmentioning
confidence: 96%
“…The recurrence rate of thermoablation is 15% after 1 year of thermoablation, while MVD shows 8.4% after 2 years of surgery [16,17].…”
Section: Discussionmentioning
confidence: 96%
“…MVD is currently recognized as the first choice for treatment of TN and its effectiveness has been confirmed ( 2 ). Nevertheless, 3-31% of patients with TN experience pain recurrence ( 4-6 ). The present study showed a 1-year recurrence rate of 23.21%.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with drug therapy, radiofrequency ablation, percutaneous balloon compression (PBC) and other methods, MVD results in longer pain-free periods and fewer side effects or complications, such as postoperative facial spasms and hearing loss (2,3). However, 3-31% of patients experience pain recurrence, which affects the quality of life and prognosis of these patients (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%